1989
DOI: 10.1182/blood.v73.6.1699.1699
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpromazine inhibits vesiculation, alters phosphoinositide turnover and changes deformability of ATP-depleted RBCs

Abstract: To delineate further the underlying mechanism by which amphiphilic drugs can modulate vesicle release from human RBCs, we studied the effect of chlorpromazine on erythrocyte vesiculation induced by ATP depletion. This was correlated with turnover of the phosphoinositides as well as RBC deformability during the process since phosphoinositide metabolism may be involved in shape regulation of RBCs. Echinocytic shape transformation and subsequent vesiculation of RBCs, which commonly occur during ATP depletion, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Trypanosome lipids were extracted with chloroform : methanol (2:1, by volume) as described before (Signorell et al, 2008a). Phospholipids were separated by two-dimensional TLC using solvent system 1 (chloroform : methanol : ammonia : water, 90:74:12:8, by volume) for the first and solvent system 2 (chlorofom : methanol : acetone : acetic acid : water, 40:15:15:12:8, by volume) for the second dimension (Bütikofer et al, 1989). On each plate, appropriate lipid standards were run alongside the samples to be analysed.…”
Section: Lipid Extraction and Phosphorous Determinationmentioning
confidence: 99%
“…Trypanosome lipids were extracted with chloroform : methanol (2:1, by volume) as described before (Signorell et al, 2008a). Phospholipids were separated by two-dimensional TLC using solvent system 1 (chloroform : methanol : ammonia : water, 90:74:12:8, by volume) for the first and solvent system 2 (chlorofom : methanol : acetone : acetic acid : water, 40:15:15:12:8, by volume) for the second dimension (Bütikofer et al, 1989). On each plate, appropriate lipid standards were run alongside the samples to be analysed.…”
Section: Lipid Extraction and Phosphorous Determinationmentioning
confidence: 99%
“…139 Vesiculation is important in a variety of hemolytic disorders. Butikofer and colleagues 140 pointed out that when RBCs are ATP-depleted, the echinocytosis that occurs may be related to the conversion of PIP 2 to phosphatidylinositol leading to spiculation (echinocytosis) of the membrane. They found that this could be inhibited by the insertion of chlorpromazine into the lipid layer of the corpuscular membrane.…”
Section: Rbc Vesiculation In Diseasementioning
confidence: 99%
“…† P р 0 . 01 compared with controls.man, 1981;Bü tikofer et al, 1989), which may point a way for the development of new therapeutic strategies.…”
mentioning
confidence: 99%